RESPON MASYARAKAT ATAS ARAH KIBLAT MAKAM: ANALISIS TERHADAP PERBEDAAN METODE PENENTUAN ARAH KIBLAT - Mega Nur Awaliah Ahmad Nur; Muh. Saleh Ridwan; Rahmatiah,HL (HISABUNA: Jurnal Ilmu Falak, 2023)
Abstract The main problem in this research is how the sensitivity of the residents towards the Qibla direction of the graves to the different methods of determining the Qibla direction in the Pangkajene Region, Pangkep Regency. This research is classified as a quantitative research with a syar'i approach and a sociological approach. In this research using population and sample. The population taken was the people of Pangkajene District, Pangkep Regency and for the sample were 45 people from 27 cemeteries. Furthermore, the data collection methods used in this study were observation, interviews, and documentation. The results of this study indicate that the residents' responses to the Qibla direction of graves in the Pangkajene Region are known to have understood that every place that wants to be built must have a Qibla direction determined, and of course in this case the measurement or determination of the orientation path. Meanwhile, the reaction of the residents of the Pangkajene Region to the different methods of determining the orientation route is known to have given good answers in addressing the use of the orientation path determinants, the pro/con reactions of the residents but the problem did not last long because the authorities, in this case the Islamic Community Guidance Center, immediately gave an understanding to the residents of the Pangkajene Region about the importance of knowing the orientation path using the orientation path determinant method. The implication of the research is that the Ministry of Religion as the government and experts who are competent in the field of Astrology who have this authority are expected to maximize socialization activities for understanding orientation paths and the use of Qibla direction determination methods in order to reduce the problems of determining Qibla direction. Keywords: Community Response, Qibla Direction Determination Method, Cemetery